Potret Penggunaan Media Televisi pada Kalangan Remaja menuju Dewasa Awal di Yogyakarta - Redatin Parwadi (MediaTor (Jurnal Komunikasi), 2005)
This research aims to know the pattern of TV media use among adolescent and pre-adult audience in Jogjakarta in terms of time-spent to watch TV, frequencies and level of attention in watching TV. Besides that, this research also aims to know in detail the background of respondents who watch TV in order to comprehend the interaction built between respondents and their parents as well as the people surrounding them. Another aims for this research are to know the most favorite program watched, the frequencies of watching television programs which contained porn and violence elements. Employing questionnaire as instrument for data collecting, this research covered no less than 750 responden which selected by stratified random sampling technique. The result of this research shows that mostly respondent (83,87 %) spending their time to watch TV in prime time range—from 17.00–22.30—a period which labeled by the community as the period of study-time. It was very reasonable to classify such audience as watchaholic—they spent no less than 180-239 minutes or 4.5 hours a day to watch TV! Most of them (72 %) were classified as avid viewer of sexual or porn element show, 57,87% frequently watch TV program containing violence elements, and 47,60 % lived in consumptive style. In general, they live with good (proper) family, even 62,40% are classified as those who consistently following religion rules.